Influencing factors systems analysis for the cultivated land protection policies implementation in China: a hybrid DEMATEL-ISM-MICMAC model - Yanwei Zhang; Xinhai Lu (Environmental Research Communications)
Cultivated land protection policies (CLPP) is an important environmental management measure in China, which not only maintains food security but also social stability. The implementation of CLPP is a systematic project, and the interrelated effects of various factors can lead to complexity. This paper identifies 38 factors influencing the CLPP implementation based on the characteristics of the policy itself, the policy system environment, the choice of policy implementation organization behavior, and the policy implementation audience. The research methods include Decision-making Trial and Evaluation Laboratory (DEMATEL), Interpretative Structural Modeling Method (ISM) and Matrix Impacts Cross-Reference Multiplication Applied to A Classification (MICMAC). The DEMATEL-ISM-MICMAC model can deeply analyze the multi-level hierarchical structure relationship among the influencing factors, the attribute categories and importance of each factor, and the influence mechanism of each factor on CLPP implementation. The results show that: (1) The 38 influencing factors interact with each other to generate a 6-level hierarchical structure model. (2) Cultivated land protection policy Implementation influence system includes 18 cause factors and 20 result factors. Among them, the family’s annual income and part-time job characteristics have a strong driving effect on other factors in the system, and policy supervision and the disclosure of policy fund accounts are easily affected by other factors. (3) Through the driving/dependency power of each factor, it can be divided into four types of factors: autonomous, dependent, linkage and independence. Among them, social norms and social networks of farmers have a strong driving effect on the improvement of policy implementation. In conclusion, the Multi-layer hierarchical structure influencing factor model used in this paper helps to deepen the research on the implementation ability of CLPP.